Status and Grass Species Diversity of Bandheli Reserve Grassland of Panchmahal District In Gujarat State, India - Patel, R M; Meena, M L (Indian Forester, 2022)
In Gujarat, a total of 8,490 km2. area under grassland falls in the eight districts. However, a systematic inventory of grassland is not yet done in the state. The present study deals with the systematic inventory of grass species diversity and characterization of Bandheli Reserve Grassland. As a result of the present investigation, a total of 60 grass species have been reported. Among the recorded 60 grass species, 18 were highly palatable, 22 are moderately palatable, nine are least palatable, and 11 are unpalatable. This entire grassland is divided into major types based on the dominant grass and its composition. This zonation will be used in its management and improvement. This grassland facing threats of converting into woodland by tree growth, i.e., out of 754.04 ha, 304 ha area covered by trees and around 100 ha is degraded. The zonation map will be helpful in the management and improvement of this grassland.